Biobehavioural approaches to prevention and treatment: A call for implementation science in obesity research. (22nd January 2020) - Kaiser, Kathryn A.; Carson, Tiffany L.; Dhurandhar, Emily J.; Neumeier, William H.; Cardel, Michelle I.
Summary: Much progress has been made in the last 30 years in understanding the causes and mechanisms that contribute to obesity, yet widely available and successful strategies for prevention and treatment remain elusive at population levels. This paper discusses the biobehavioural framework and provides suggestions for applying it to enable greater progress in the science of obesity prevention and treatment, including an increased focus on implementation of science strategies. The objective is to promote a re‐evaluation of current views about preventing and treating obesity within a unified biobehavioural framework. Further integration of research exploring how both behavioural and biological components interact is a critical step forward.